BRAIN HEALTH CARE THROUGH NEUROBIC ACTIVITY FOR ELDERLY - Kritpet, Thanomwong; Napatpittayatorn, Phubate (Journal of Sports Science and Health, 2021)
Thailand has completely entered the aging society. Hences, taking care of the elderly health is very important due to degenerative changes occur with aging in all organ systems especially, the deterioration of the brain. Therefore, the brain health care is necessary for seniors. Neurobic activities is an effective alternative strategy in delaying brain’s functional decline in elderly especially for attention and memory. The neurobic activity can enhance the nerve impulse and interconnections among different neurons to function together. As a result, the brain works more efficiently. Neurobic activity can be conducted by changing the habitual sensory inputs including sound, sight, smell, taste, and touch. For instance, changing to some new unusual life style, or breaking daily routines in a different way, and soon. Collectively, neurobic activity is beneficial to promote the brain functions as well as to enhance quality of life in elderly.